3=-4n+3n

Simple and best practice solution for 3=-4n+3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=-4n+3n equation:


Simplifying
3 = -4n + 3n

Combine like terms: -4n + 3n = -1n
3 = -1n

Solving
3 = -1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'n' to each side of the equation.
3 + n = -1n + n

Combine like terms: -1n + n = 0
3 + n = 0

Add '-3' to each side of the equation.
3 + -3 + n = 0 + -3

Combine like terms: 3 + -3 = 0
0 + n = 0 + -3
n = 0 + -3

Combine like terms: 0 + -3 = -3
n = -3

Simplifying
n = -3

See similar equations:

| 2(j-3)=9(6-3j)+10j | | 9x^2+26x+17=0 | | 3p+6=2p+10 | | 20(y+2)=4y+5 | | 2j-6=54-27j+10j | | x-34=-14 | | 4X-30+X+20=180 | | 8x^3-60x^2+150x-854=0 | | x-27=-17 | | -27=-5(9a+6) | | 12+8r=6-10r | | 10x+3(4x-2)=6 | | 7y+3(y-6)=6(y+1)-3 | | 12x-(8x-9)=45 | | 6x-7x+2=12 | | 2x-8+10=3x-7 | | 5*sin(14x)=5*cos(7x) | | 13x^2-8x-20=0 | | -2y+9x=3 | | -14+74=-5(x+3) | | 3y^2-4=y | | 2(4z+2)-6=70 | | 3(t+2)=7(7-t)-9 | | 3x-4x+5=54 | | 3m+6=37 | | 12-2a=18 | | 4.75=1.75+1a | | 20X+32=0 | | 60=32-4(x-3) | | 3x+4z=13 | | x=16+5n | | -3y=15-2x |

Equations solver categories